2006
DOI: 10.1128/jvi.01709-06
|View full text |Cite
|
Sign up to set email alerts
|

Proviral Progeny of Heterodimeric Virions Reveal a High Crossover Rate for Human Immunodeficiency Virus Type 2

Abstract: Human immunodeficiency virus type 1 (HIV-1), the causative agent of AIDS in humans, exhibits a very high rate of recombination. Bearing in mind the significant epidemiological and clinical contrast between HIV-2 and HIV-1 as well as the critical role that recombination plays in viral evolution, we examined the nature of HIV-2 recombination. Towards this end, a strategy was devised to measure the rate of crossover of HIV-2 by evaluating recombinant progeny produced exclusively by heterodimeric virions. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…For both HIV-1 and gammaretroviruses, reducing RNase H activity decreased template switching (37,234). These findings suggested that retroviruses with low RNase H activity, such as HIV-2 (132), would recombine less frequently than HIV-1, which possesses robust RNase H. However, subsequent studies demonstrated that rates of template switching are very similar for HIV-2 and HIV-1 (50,221).…”
Section: Enzymology Of Recombinationmentioning
confidence: 60%
See 2 more Smart Citations
“…For both HIV-1 and gammaretroviruses, reducing RNase H activity decreased template switching (37,234). These findings suggested that retroviruses with low RNase H activity, such as HIV-2 (132), would recombine less frequently than HIV-1, which possesses robust RNase H. However, subsequent studies demonstrated that rates of template switching are very similar for HIV-2 and HIV-1 (50,221).…”
Section: Enzymology Of Recombinationmentioning
confidence: 60%
“…Other evidence comes from observations that recombination is fully as frequent when only minus-strand recombination is possible as when both minus-and plus-strand recombination could contribute (12,148,355,359). Another argument against significant plus-strand recombination lies in the very high frequency of minus-strand crossovers, because the template degradation which that would require precludes extensive plus-strand diploidy (221). Nonetheless, "backwards" insertions have been observed for both experimental replication products and clinical isolates (87, 311; see discussion in reference 314).…”
Section: Models For Retroviral Genetic Recombinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombination can occur between highly related viruses to reassort sequences, thereby increasing the diversity of the population and allowing the emergence of variants that are most fit for the particular selection pressures at a given time (2,11,13,16,27,28,33,37,(39)(40)(41)47). Recombination can also occur between genetically similar viruses that are further apart in sequence identity than those in a viral population.…”
mentioning
confidence: 99%